2013
DOI: 10.1088/1475-7516/2013/04/007
|View full text |Cite
|
Sign up to set email alerts
|

Direction dependence of the power spectrum and its effect on the cosmic microwave background radiation

Abstract: We study several anisotropic inflationary models and their implications for the observed violation of statistical isotropy in the CMBR data. In two of these models the anisotropy decays very quickly during the inflationary phase of expansion. We explicitly show that these models lead to violation of isotropy only for low l CMBR modes. Our primary aim is to fit the observed alignment of l = 2, 3 multipoles to the theoretical models. We use two measures, based on the power tensor, which contains information abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…It has also been suggested that this anisotropy may not really be in disagreement with the inflationary Big Bang cosmology, which may have a phase of anisotropic and inhomogeneous expansion at very early time. The anisotropic modes, generated during this early phase may later re-enter the horizon [51,52] and lead to the observed signals of anisotropy.…”
Section: Introductionmentioning
confidence: 94%
“…It has also been suggested that this anisotropy may not really be in disagreement with the inflationary Big Bang cosmology, which may have a phase of anisotropic and inhomogeneous expansion at very early time. The anisotropic modes, generated during this early phase may later re-enter the horizon [51,52] and lead to the observed signals of anisotropy.…”
Section: Introductionmentioning
confidence: 94%
“…3 This form of the correlation has slight difference from the original one in Ref. [29]. Here, we have only extracted the anisotropic effects.…”
Section: The "Power Tensor" Techniquementioning
confidence: 95%
“…It refers to the correlator of two power tensors with different multipoles [29]. Thus, the correlation of two power tensors is defined as…”
Section: The "Power Tensor" Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The precise operator that should arise while computing the power spectrum must be consistently prescribed by the underlying field theory. One may, for example, use perturbation theory [21,53] and compute the corrections to the power spectrum arising due to noncommutative space-time order by order in the noncommutative parameter, θ 0 . This is rather complicated and we postpone this detailed calculation to future research.…”
Section: A Model Power Spectrum In Noncommutative Space-timementioning
confidence: 99%